Aesthetic Temporalities Today: Present, Presentness, Re-Presentation - Stercken, Angela; Genge, Gabriele; Schwarte, Ludger (transcript, 2020)
This volume is dedicated to the interrelation between temporality and representation. It presumes that time cannot be conceived of as an abstract chronometric order, but that it is referring to materiality, being measured, represented, expressed, recognized, experienced and evaluated, and therefore is always closely related to cultural contexts of perception and evaluation.The contributions from various disciplines are dedicated to the present and its plural conditions and meanings. They provide insights into the state of research with special emphasis on the global present as well as on art and aesthetics from the 18th century until today.The anthology includes contributions by Mieke Bal, Stefan Binder, Maximilian Bergengruen, Iris Därmann, Gabriele Genge, Boris Roman Gibhardt, Boris Groys, Maria Muhle, Johannes F. Lehmann, Nkiru Nzegwu, Francesca Raimondi, Christine Ross, Ludger Schwarte, Angela Stercken, Samuel Strehle, Timm Trausch, Patrick Stoffel, and Christina Wessely.